2019
DOI: 10.1016/j.amsu.2019.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral inguinal bladder hernia following unilateral transabdominal preperitoneal repair. A case report and review of the literature

Abstract: Sliding hernia occurs when the hernia sac is partially formed by the wall of a viscus. The most common components of a sliding hernia includes the sigmoid colon, cecum, appendix, urinary bladder, and the ascending colon. However, the presence of bilateral vesical sliding hernia is rare and few cases have been reported in the literature. Patients with vesical sliding hernia may present with groin swelling with an associated lower urinary tract symptom. Computed tomography (CT) scan is the modality of choice for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Bei den seltenen beidseitigen Blasenhernien erkennt man im CT das sog. "Pelvic oder perineal Mickey Mouse Sign" [10,12,17,22], welches erstmals 2013 von Sagar A et al beschrieben wurde [17]. Man erkennt im Transversalschnitt die beidseitigen Ausstülpungen der Blasenwand in den Leistenkanal, sodass diese, die Ohren der Comicfigur und die Harnblase selbst, den Kopf nachahmen.…”
Section: Patientunclassified
“…Bei den seltenen beidseitigen Blasenhernien erkennt man im CT das sog. "Pelvic oder perineal Mickey Mouse Sign" [10,12,17,22], welches erstmals 2013 von Sagar A et al beschrieben wurde [17]. Man erkennt im Transversalschnitt die beidseitigen Ausstülpungen der Blasenwand in den Leistenkanal, sodass diese, die Ohren der Comicfigur und die Harnblase selbst, den Kopf nachahmen.…”
Section: Patientunclassified
“…Surgeons should use their experience to decide which procedure to use. Meanwhile, there are concerns about intraoperative bladder injury during laparoscopic surgery due to technical difficulties [ 16 , 17 ]. Therefore, further studies are needed to clarify the superiority of laparoscopic herniorrhaphy for inguinal bladder hernia.…”
Section: Discussionmentioning
confidence: 99%
“…Nasser et al have reported a similar case in the literature. They managed the patient surgically with bilateral open Lichtenstein tension free repair with a successful outcome [11].…”
Section: Discussionmentioning
confidence: 99%